KRIM KAMUFLASE BERBASIS SAMBILOTO (ANDROGRAPHIS PANICULATA): INOVASI SEDIAAN TOPIKAL MULTIFUNGSI UNTUK PROTEKSI KULIT MILITER - Aisyah Putri Rifdiningsih; Naurah Salsabila; Rinda Dwi Sartika (Bajang Institute, 2026)
The extreme military operational environment is prone to triggering various dermatological disorders in personnel due to exposure to ultraviolet (UV) radiation, high temperatures, humidity, dust, microorganisms, and mechanical friction. Camouflage creams are commonly used for visual concealment, but conventional formulations often overlook the aspect of biological skin protection. Sambiloto (Andrographis paniculata), a native Indonesian plant, has the potential to be innovated as an active ingredient in topical preparations because it is rich in secondary metabolites with anti-inflammatory and antioxidant activities. This article aims to review the potential of Sambiloto extract in developing a multifunctional camouflage cream for military skin protection. The method used is a narrative review through a comprehensive scientific literature search spanning the years 2018-2026. The results show that the main bioactive compound of Sambiloto, andrographolide, effectively controls inflammation, reduces oxidative stress, and protects skin tissue from external damage. The development of this Sambiloto-based camouflage cream offers an innovative approach that integrates tactical function (concealment) and medical function (topical preparation protection). Furthermore, the utilization of this plant supports national raw material independence based on local biological resources. Despite its potential, further experimental research regarding formulation optimization, stability, and clinical trials is highly required to ensure its field efficacy and safety.